Optimising environmental design strategies to improve thermal performance in office buildings in Kenya - Kiamba, Lorna Ndanu (2016)
An examination of contemporary office buildings in the warm humid region of Kenya revealed the predominance of highly glazed lightweight buildings that are prone to overheating and rely on costly and unsustainable active climate control systems. In the midst of growing energy demand and a potential deficit in supply, the influx of these poorly designed buildings has intensified the need to explore viable climate-responsive design alternatives suitable to local conditions that can extend occupant comfort and reduce the need for energy intensive environmental control systems. This view is shared by the Kenyan government which has set ambitious targets to develop and enforce national codes for energy efficiency and conservation in buildings by 2030. However, despite the clear and urgent need, research shows that little work has been developed to date that can be applied to the Kenyan context and climate. In this research, ways of improving the thermal comfort and performance of office buildings in the warm humid city of Mombasa (latitude 4°S) were explored. The work was developed through a series of field studies of local vernacular and modern case study buildings and subsequent computer simulations. From this, vernacular Swahili-inspired design strategies were derived and the application of the potentially most significant mitigation strategy to typical local office buildings examined further. Although other work exists elsewhere that may be comparable to parts of this study, this is the first effort that brings together the post occupancy evaluation of buildings in Mombasa, a thorough investigation of the effectiveness of the vernacular strategies found in Swahili architecture, and the validation of the application of these strategies to modern offices. Initial findings derived from a parametric study revealed external shading to be the most effective design strategy as it alleviated solar heat gain transmitted through glazing into buildings, resulting in a significant reduction in discomfort hours. Subsequently, using a series of dynamic computer simulations run for a typical office building in Mombasa, the average monthly solar heat gain coefficient (SHGC) values were derived for a typical year. These previously unavailable latitude (and hemisphere) specific solar path indices were deemed critical in the provision of essential data for effective external shading device design. The findings indicated that low SHGC values of under 0.5 gave the general indication of low percentage of discomfort hours (under 10%). Additionally, estimates of potential annual cooling energy savings of up to 60% were made based on the reduction of SHGC values for shading elements of practicable size. The application of these study findings to two local office buildings revealed that the derived SHGC values and energy estimates provide useful references when considered for similar type office buildings on similar latitudes. For both buildings, it was predicted that energy savings of 15% to 61% could be achieved from the application of suitably sized external shading devices. It was suggested that this type of information would encourage designers to use external shading devices as a method of maintaining thermal comfort, conserving energy and lowering operating costs in office buildings. Finally, recommendations for the incorporation of minimum shading standards in building regulations have been made and presented in a design guidance document.